Identification of Endoparasites in Cork Fish (Channa striata) from Peat Swamp Waters of Palangka Raya City, Central Kalimantan - Maryani, Maryani; Rosita, Rosita; Rusmini, Rusmini (Universitas Batangahari Jambi, 2025)
This study aims to determine the type of endoparasites that infect snakehead fish and determine the level of prevalence, intensity, and dominance of endoparasites from peat swamp waters. This research was conducted on 15 February - 15 March 2023 for 1 month at the Fish Quarantine Station Quality Control and Safety of Fishery Products in Palangka Raya. The research method used is descriptive research method. As a result of the assistance, 7 types of endoparasites were found, namely Neoechinorhynchus sp., Camallanus sp., Procamallanus sp., Strongyloides sp., Eustrongyloides sp., Proteocephalus sp., and Senga sp. which is found in the target organs of meat, liver, stomach and intestines